Vanellus chilensis subsp. chilensis chilensis (Molina 1782 - Gonza ́ Lez-Acun, Daniel A.; Palma, Ricardo L. (Zenodo, 2021)
Vanellus chilensis chilensis (Molina, 1782) Southern lapwing—Queltehue Actornithophilus gracilis (Piaget, 1880) Austromenopon aegialitidis (Durrant, 1906) sensu lato Quadraceps guimaraesi Timmerman, 1954 Published as part of Gonza ́ Lez-Acun, Daniel A. & Palma, Ricardo L., 2021, An annotated catalogue of bird lice (Insecta: Phthiraptera) from Chile, pp. 1-151 in Zootaxa 5077 (1) on page 124, DOI:10.11646/zootaxa.5077.1.1, http://zenodo.org/record/5766642